Sams teach yourself WordPress in 10 minutes - Tomasi, Chuck (Sams teach yourself., 2010)
Sams Teach Yourself WordPress in 10 Minutes Chuck Tomasi Kreg Steppe Sams Teach Yourself WordPress in 10 Minutes gives you straightforward, practical answers when you need fast results. By working through its 10-minute lessons, you'll learn everything you need to build great blogs with WordPress and WordPress.org, and reach any audience by web browser, RSS, or cell phone! Tips point out shortcuts and solutions Cautions help you avoid common pitfalls Notes provide additional information Plain English definitions explain new terms 10 minutes is all you need to learn how to ... Quickly build blogs for free with WordPress.com Customize your blog to fit your message Create powerful text, audio, and video content Moderate comments and build communities Set up RSS feeds Host your own blog with WordPress.org software Deliver content via iPhone and BlackBerry Streamline publishing with third-party tools Register your book at informit.com/register for convenient access to updates and corrections as they become available. Category: Internet Covers: WordPress User Level: Beginning.